The pathophysiology of traumatic brain injury at a glance - Mayumi Prins; Tiffany Greco; Daya Alexander; Christopher C. Giza (The Company of Biologists, 2013)
Traumatic brain injury (TBI) is defined as an impact, penetration or rapid movement of the brain within the skull that results in altered mental state. TBI occurs more than any other disease, including breast cancer, AIDS, Parkinson's disease and multiple sclerosis, and affects all age groups and both genders. In the US and Europe, the magnitude of this epidemic has drawn national attention owing to the publicity received by injured athletes and military personnel. This increased public awareness has uncovered a number of unanswered questions concerning TBI, and we are increasingly aware of the lack of treatment options for a crisis that affects millions. Although each case of TBI is unique and affected individuals display different degrees of injury, different regional patterns of injury and different recovery profiles, this review and accompanying poster aim to illustrate some of the common underlying neurochemical and metabolic responses to TBI. Recognition of these recurrent features could allow elucidation of potential therapeutic targets for early intervention.